Assessing apathy in everyday clinical practice with the short‐form Lille Apathy Rating Scale. Issue 14 (8th July 2013) - Dujardin, Kathy; Sockeel, Pascal; Carette, Anne‐Sophie; Delliaux, Marie; Defebvre, Luc
ABSTRACT Background Apathy is an invalidating behavioral disorder that must always be screened for and assessed in patients with Parkinson's disease (PD). The Lille Apathy Rating Scale (LARS) has been validated in several different contexts, but the lengthy administration time means that it is mostly recommended for research use. The aim of the present study was to validate a short form of the LARS for use in everyday practice. Methods In total, 416 patients with PD and 56 healthy controls participated in the study. Apathy, depression, motor symptoms, and overall cognitive efficiency were assessed. The most discriminant items of the LARS for apathy detection were selected using multiple indicators. Results A subset of 12 items (constituting the short‐form LARS) showed the best convergence. Concurrent and criterion‐related validity, internal consistency, test‐retest reliability, and inter‐rater reliability were very good. Conclusions The short‐form LARS is a reliable, practical, patient interview‐based instrument for assessing apathy in everyday clinical practice. © 2013 International Parkinson and Movement Disorder Society